2014
DOI: 10.1002/cphc.201402137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Perovskites as Electrocatalysts for the Oxygen Evolution Reaction

Abstract: The oxygen evolution reaction (OER) is an enabling process for technologies in the area of energy conversion and storage, but its slow kinetics limits its efficiency. We performed an electrochemical evaluation of 14 different perovskites of variable composition and stoichiometry as OER electrocatalysts in alkaline media. We particularly focused on improved methods for a reliable comparison of catalyst activity. From initial electrochemical results we selected the most active samples for further optimization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 32 publications
0
80
0
Order By: Relevance
“…Compared to the dramatic increase for the BSCF perovskite oxide with the addition of carbon, these results therefore indicate only a fair interaction between LSCF and AB f occurred as recently described. 38 PBCO and PBCO/AB f .- Figure 4a and 4b) finally illustrate the ohmic-drop corrected anodic CV scans for the OER activity with a close up for each in the capacitive region given in Figure 4c and 4d for PBCO and PBCO/AB f electrodes, respectively. Figure 4e and 4f) show the capacity-and ohmic-drop-corrected Tafel plots of the pure PBCO electrode and PBCO/AB f composite electrodes in the OER potential regime (1.0-1.7 V vs. RHE).…”
mentioning
confidence: 85%
“…Compared to the dramatic increase for the BSCF perovskite oxide with the addition of carbon, these results therefore indicate only a fair interaction between LSCF and AB f occurred as recently described. 38 PBCO and PBCO/AB f .- Figure 4a and 4b) finally illustrate the ohmic-drop corrected anodic CV scans for the OER activity with a close up for each in the capacitive region given in Figure 4c and 4d for PBCO and PBCO/AB f electrodes, respectively. Figure 4e and 4f) show the capacity-and ohmic-drop-corrected Tafel plots of the pure PBCO electrode and PBCO/AB f composite electrodes in the OER potential regime (1.0-1.7 V vs. RHE).…”
mentioning
confidence: 85%
“…[6][7][8][9][10][11][12][13][14][15] In contrast, several perovskites used as single material electrodes, both in the form of powders or thin fi lms, have shown relatively modest performance compared to the respective perovskite/carbon composite electrodes. [10][11][12][13][14][15][16][17] It is generally argued that carbon is needed in the perovskite-based electrodes to improve the electrical connection between particles and agglomerates, even though several recent literature reports have shown that carbon may play a more complex role as just a simple conductive support. [ 11,12,14,15,17 ] Therefore, understanding why carbon can act as activity booster for the electrochemical activity of some perovskite oxides is crucial, both from a fundamental point of view and for the rational design of better perovskite-based electrocatalysts.…”
mentioning
confidence: 92%
“…[1][2][3][4][5][6][7] Next to scarce noble metal oxides, several first-row transition metal oxides and, in particular, perovskite-based systems with the general formula ABO 3 perform well as OER catalysts. [6][7][8][9][10] Theoretical studies suggest that the catalytic activity of the four-electron transfer reaction forming molecular O 2 depends on strength and flexibility of the metal-oxygen bond, which can shift the redox activity from metal to lattice oxygen surface sites due to ligand hole formation. [7,28,34,39,40] Thus, an understanding of the underlying microscopic mechanisms, the nature of active sites, and catalyst stability is necessary to rationalize the search for active and stable catalysts.…”
Section: Introductionmentioning
confidence: 99%